Mad Max. Fury Road [videorecording (DVD)] - Miller, George, 1945 March 3-; McCarthy, Brendan; Lathouris, Nico; Hardy, Tom, 1977-; Theron, Charlize; Hoult, Nicholas, 1989-; Keays-Byrne, Hugh, 1947-2020; Huntington-Whiteley, Rosie, 1987-; Keough, Riley, 1989-; Kravitz, Zoë, 1988-; Abbey Lee, 1987-; Eaton, Courtney, 1996-; et al. (Warner Bros. Home Entertainment, Inc., 2015)
A return to the world of the Road Warrior, Max Rockatansky. Haunted by his turbulent past, he believes the best way to survive is to wander alone. Nevertheless, he becomes swept up with a group fleeing across the Wasteland in a War Rig driven by an elite Imperator, Furiosa. They are escaping a Citadel tyrannized by the Immortan Joe, from whom something irreplaceable has been taken. Enraged, the Warlord with his gangs, pursues the rebels ruthlessly in the high-octane Road War that follows.